Amino-functionalized Cu for efficient electrochemical reduction of CO to acetate - Wang, Yinyin (2023)
Electrosynthesis of valuable chemicals from carbon dioxide (CO2) or carbon monoxide (CO) offers a promising strategy for the storage of renewable electricity and at the same time reduces carbon emission. However, the catalyst’s activity and selectivity need significant improvements, and the exact mechanism of the reaction is still elusive. Herein, we report selective electrochemical reduction of CO to acetate on an amino functionalized Cu surface (Cu@NH2) derived from in situ electroreduction of copper ammonia chloride complexes. At a potential of −0.75 V versus the reversible hydrogen electrode (RHE), the Cu@NH2 exhibits significant catalytic performance of CO electroreduction with a CO-to-acetate Faradaic efficiency (FE) of 51.5% and an acetate partial current density of around 150 mA cm-2. Based on a combination of in situ spectroscopy studies and DFT calculations, it is found that the amino groups on the Cu surface are valuable for maintaining the low valence state of Cu, and the Hδ+ in the amino groups can stabilize the oxygen-containing intermediates through hydrogen bonding, which effectively increases the coverage of *CHO on the catalyst’s surface, thereby facilitating the *CO-*CHO coupling to acetate.